2011
DOI: 10.1002/ibd.21400
|View full text |Cite
|
Sign up to set email alerts
|

Short CDAI: Development and validation of a shortened and simplified Crohnʼs disease activity index

Abstract: The short CDAI is a valid, reliable, and responsive tool for the measurement of CD activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 20 publications
0
71
0
1
Order By: Relevance
“…The CDAI has evolved as the gold standard for clinical trials 4. Although the CDAI may be adequate for measuring disease activity in some circumstances, it has some important limitations including the fact that approximately 40% of the index is derived from three subjective criteria (diarrhoea, abdominal pain and sense of well-being) which account for 80% of the responsiveness to change,2 while it does not take into account the more objective measures of inflammation (such as C-reactive protein (CRP) and endoscopic lesions) in a disease which is by definition inflammatory in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The CDAI has evolved as the gold standard for clinical trials 4. Although the CDAI may be adequate for measuring disease activity in some circumstances, it has some important limitations including the fact that approximately 40% of the index is derived from three subjective criteria (diarrhoea, abdominal pain and sense of well-being) which account for 80% of the responsiveness to change,2 while it does not take into account the more objective measures of inflammation (such as C-reactive protein (CRP) and endoscopic lesions) in a disease which is by definition inflammatory in nature.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Knowing patients' CD activity is of great importance in clinical practice as well as medical research. Two studies have thus far developed a shortened assessment of CD activity derived from the CDAI 13,14 with the aim of easing the use of the CDAI in research. However, these short indices still require that patients record and sum up their disease activity for 7 consecutive days using a disease activity diary.…”
mentioning
confidence: 99%
“…The Crohn's disease activity index (CDAI) has evolved as the gold standard for clinical trials [12], but analysis of data from a large, prospective, well-defined subpopulation of the SONIC trial [13] showed that CDAI was not accurate to predict C-reactive protein (CRP) normalization and/or mucosal healing in CD as half the patients with CD in clinical remission had endoscopic and/or CRP evidence of residual active CD [14]. Objective outcome measures of CD activity, in addition to assessment of clinical symptoms, are obviously needed to evaluate disease activity in CD.…”
Section: Monitoring Disease Activity In Crohn's Diseasementioning
confidence: 99%